2017
DOI: 10.1371/journal.pbio.2003790
|View full text |Cite
|
Sign up to set email alerts
|

The sea cucumber genome provides insights into morphological evolution and visceral regeneration

Abstract: Apart from sharing common ancestry with chordates, sea cucumbers exhibit a unique morphology and exceptional regenerative capacity. Here we present the complete genome sequence of an economically important sea cucumber, A. japonicus, generated using Illumina and PacBio platforms, to achieve an assembly of approximately 805 Mb (contig N50 of 190 Kb and scaffold N50 of 486 Kb), with 30,350 protein-coding genes and high continuity. We used this resource to explore key genetic mechanisms behind the unique biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
183
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(189 citation statements)
references
References 101 publications
4
183
0
2
Order By: Relevance
“…Interestingly, in some cases, the SHSPs of the acorn worm grouped with the counterparts of echinoderms. This finding is consistent with the conclusion of Zhang et al, which suggested that echinoderms and hemichordates were sister groups and shared a common ancestor (Zhang et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, in some cases, the SHSPs of the acorn worm grouped with the counterparts of echinoderms. This finding is consistent with the conclusion of Zhang et al, which suggested that echinoderms and hemichordates were sister groups and shared a common ancestor (Zhang et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The Latin name of each species is listed in Appendix: Supplementary Table S3. hemichordates were sister groups and shared a common ancestor (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The c25145 gene encodes a putative evolutionarily-conserved protein with an unknown function as deduced from the alignment of the Hydra c25145 deduced protein product with related bilaterian sequences ( Fig S4 ). We found similarities in the N-terminal moiety (~100 first amino acids) with hypothetical proteins expressed by the sea cucumber Apostichopus japonicus (51), the arthropods Folsomia candida and Sipha flava (aphid), the mollusc Crassostrea gigas , the teleost fish Myripristis murdjan, Sinocyclocheilus rhinocerous or Danio rerio . Within this domain, a signature can be identified, formed of 37 residues, from which 32 are present in the Hydra protein ( Fig S4 ).…”
Section: Resultsmentioning
confidence: 88%
“…However, only one QTL for growth was reported (Tian et al, ) and none GWAS has been conducted in sea cucumber A. japonicus . Recently, the whole genome sequences of A. japonicus have been published and a database was established (Zhang et al, ), which will carry forward QTL analysis and candidate gene identification in sea cucumber A. japonicus .…”
Section: Introductionmentioning
confidence: 99%